ON THE INFLUENCE OF DIFFUSION STABILIZATION IN OLDROYD-B FLUID FLOW SIMULATIONS - Pires, Marília (2021)
This work presents some numerical tests of finite element solution of incompressible Oldroyd-B fluid flows. The effect of numerical stabilization using arti cial stress diffusion is investigated in detail. The limits of Weissenberg number We for which is possible to obtain the numerical solution were studied depending on the Reynolds number Re and the diffusion parameter. Series of numerical tests was performed for steady two-dimensional Oldroyd-B fluid flow in corrugated channel (tube). The numerical results clearly proved the advantage (higher attainable We) of stabilized numerical method over the classical formulation without the arti ficial stress diffusion.